Identification guides British and European rocks and minerals - Fejer, E.; Fitzsimons, C.; Frampton, S. (London : Frame Tree Pub., 2007)
An illustrated identification guide that profiles the most common rocks and minerals in Britania and Europe.
Keywords: Minerals -- Britania; Minerals -- Europe; Rocks -- Britania; Rocks -- Europe